(untitled) (Eurasian Medical Research Periodical, 2023)
Novel coronavirus pneumonia is a type of viral inflammation of the lungs. Viral pneumonias are already known to us, but we were not used to working with them in such large numbers as now. The conditions of the SOVID-19 pandemic made the statistics of this type of pneumonia very high. In the early years of the pandemic, about 20-25 percent of patients with COVID-19 developed pneumonia, and this rate increased even more after the "delta" strain became the dominant version. The purpose of our research is to develop measures to prevent the spread of pneumonia and complications of this disease in the context of the COVID-19 pandemic. We have set ourselves the task of providing an understanding of the nature of the infection with the coronavirus and developing tactics for the treatment of this infection